Padang Tok Sheikh quarzite heritage mapping using digital close range photogrammetry / Noor Syahirah Zaludin - Zaludin, Noor Syahirah (2020)
Mapping is strongly related to the survey practice, a practice in which points related to each other are determined and recorded. Digital terrain model and digital surface model methods, close-range photogrammetry provide a height of the area for. The previously there are no expose about the survey and standard architectural representation typically consist of object visualizations consisting of plans, sections, profiles and rectified pictures. Unmanned aerial vehicles (UAV) to take the photo by using the photogrammetry. It making measurements from photographs. The instrument manufactured for UAV could be mounted on unmanned flying platforms of various size and type. The study focussing on mapping and elevation of the site. This study also to produce the orthophoto mapping. The Aim of this study is to generate the map of Padang Tok Sheikh quarzite Gunung Jerai. To achieve the aim, the objective of the study are to generate the orthophoto images mapping using UAV aerial images. To analyse capability of Digital Surface Model and Digital Terrain Model. For data, in this project by using aerial photogrammetry image. Study area of this study at Padang Tok Sheikh Gunung Jerai, Kedah. The methodology, collect the data from flying drone at the study area. In this study, also use Agisoft Photoscan Software to process the aerial photo around the area. Arcgis software also use to generate the mapping production. The final product also include to model the digital surface model and digital terrain model at Padang Tok Sheikh quarzite Gunung Jerai.